Manajemen Kebudayaan Pesantren Pascamodern di Indonesia - Chusnul Chotimah; Ahmad Natsir; Syahril Siddiq (Muslim Heritage, 2023)
AbstractThis paper aims to analyze how Islamic boarding schools can survive in a constantly changing world and what is the secret behind the ability of Islamic boarding schools to adapt to increasingly rapid developments and open information systems. Such significant challenges of the times force pesantren to choose one of two things, to be left behind or to change to adapt. This study chose the locus at the Amanatul Ummah Islamic Boarding School located in Pacet Mojokerto because the pesantren's policies are closely related to survival efforts over the current developments. After this research was carried out, it showed that, on the one hand, Islamic boarding schools have limited infrastructure. On the other hand, they are subject to government pressure and community demands to adapt to changes and meet applicable standards. Two reasons are the answer to the survival of pesantren. First, Al-muá¸¥Äfaáº“ah 'alÄ al-qadÄ«m al-á¹£Äliá¸¥ wa al-ahdz bi al-jadÄ«d al-aá¹£laá¸¥ has become a value basis for the contextual transformation of pesantren. Second, the cultural management of the pesantren can be seen from the ability of the pesantren to carry out religious and cultural missions that negotiate with science and technology. Modernity management in Islamic boarding schools is a starting point for a pesantren continually to evaluate and then change with the note that it maintains the traditional values of the pesantren as keeping the faith, which is the finding in this study. This paper suggests the need for institutional standardization of Islamic boarding schools to achieve the mission of making Islamic boarding schools a centre for the development of education and civilization.Â AbstrakTulisan ini bertujuan untuk menganalisis bagaimana pesantren dapat bertahan dalam dunia yang terus berubah, apa rahasia di balik kemampuan pesantren beradaptasi dengan perkembangan zaman yang semakin pesat dan sistem informasi yang terbuka. Tantangan zaman yang demikian besar memaksa pesantren untuk memilih satu di antara dua hal, ketertinggalan, atau berubah untuk menyesuaikan. Penelitian ini memilih lokus di Pesantren Amanatul Ummah yang berlokasi di Pacet Mojokerto dengan alasan kebijakan pesantren yang lekat dengan upaya survival atas perkembangan zaman yang ada. Setelah penelitian ini dilakukan, penelitian ini menunjukan bahwa pesantren di satu sisi memiliki keterbatasan infrastruktur, di lain sisi mendapatkan tekanan pemerintah dan permintaan masyarakat untuk menyesuaikan diri dengan perubahan Â dan memenuhi standar yang berlaku. Dua alasan menjadi jawaban kelangsungan hidup pesantren. Pertama, Al-muá¸¥Äfaáº“ah 'alÄ al-qadÄ«m al-á¹£Äliá¸¥ wa al-ahdz bi al-jadÄ«d al-aá¹£laá¸¥ telah menjadi basis nilai bagi transformasi pesantren secara kontekstual. Kedua, manajemen kebudayaan pesantren yang tampak dari kemampuan pesantren menjalankam misi agÃ ma dan kebudayaan yang bernegosiasi dengan ilmu pengetahuan dan teknologi. Modernity management di pesantren menjadi sebuah titik pijakan sebuah pesantren untuk selalu malakukan evaluasi kemudian berubah dengan catatan tetap menjaga nilai tradisi pesantren sebagai keeping faith menjadi temuan dalam penelitian ini. Tulisan ini menyarankam perlunya standarisasi kelembagaan pesantren agar tercapai misi menjadikan pesantren sebagai pusat perkembangan pendidikan dan peradÃ ban.